New records of Pauropoda (Myriapoda) with descriptions of new taxa - Scheller, Ulf (Zootaxa, 2014)
Nine species new to science are described, five species in Pauropodidae: Allopauropus circulus n. sp. from France, Decapauropus extremus n. sp. from Mexico, D. pyriformis n. sp. from Italy, Stylopauropus laminatus n. sp. from Thailand, S. longus n. sp. from Siberia; one in Brachypauropodidae: Mojingapauropus biappendiculatus n. gen., n. sp. from Panama; one species in Eurypauropodidae Trachypauropus lusitanicus n. sp. from Portugal; and two species in Sphaeropauropodidae: Sphaeropauropus exilis n. sp. from Papua New Guinea and S. rotatilis n. sp. from China. Pauropoda are reported for the first time from New Guinea. New collecting sites are given for 69 species.